ПЛАТА ЗА ЗЕМЛЮ В СИСТЕМІ МАЙНОВОГО ОПОДАТКУВАННЯ: ОСОБЛИВОСТІ СПРАВЛЯННЯ В УКРАЇНІ ТА КРАЇНАХ ЄС - Патицька, Христина Олегівна (Науковий журнал «Світ фінансів», 2019)
Патицька Х. О. Плата за землю в системі майнового оподаткування: особливості справляння в Україні та країнах ЄС.Досліджено місце і роль плати за землю як майнового податку в складі доходів місцевих бюджетів в Україні та окремих державах ЄС. Визначено особливості механізму податку на землю в цих країнах. Досліджено основні аспекти справляння плати за землю в розрізі визначення податкової бази, проведення оцінки бази оподаткування, встановлення податкових ставок і визначення рівня та особливостей управління при оподаткуванні землі. Здійснено порівняння механізмів справляння податку на землю в Україні та окремих каїнах ЄС. На підставі проведеного дослідження сформульовано конкретні рекомендації та пропозиції щодо вдосконалення адміністрування плати за землю в Україні. Патицкая К. О. Плата за землю в системе имущественного налогообложения: особенности взимания в Украине и странах ЄС.Исследовано место и роль платы за землю как имущественного налога в составе доходов местных бюджетов в Украине и отдельных государствах ЕС. Определены особенности механизма налога на землю в этих странах. Исследованы основные аспекты взимания платы за землю в разрезе определения налоговой базы, проведения оценки базы налогообложения, установления налоговых ставок и определения уровня и особенностей управления при налогообложении земли. Проведено сравнение механизмов взимания налога на землю в Украине и отдельных странах ЕС. На основании проведенного исследования сформулированы конкретные рекомендации и предложения по совершенствованию администрирования платы за землю в Украине. Patytska K. Land tax in the system of property taxation: specifics administration in Ukraine and EU countries.Introduction. Problems of local budgeting in Ukraine, lack of financial resources of local authorities and instability of their revenue have been quite topical and still unsolved. Like most countries that emerged from the former Soviet Union, Ukraine has faced very substantial difficulties in maintaining economic growth while at the same time organizing an effective local government and fiscal structure and administration. An important aspect of this task has been to establish clearly defined property rights, including those in land, in order to facilitate market activities while also providing an appropriate fiscal base for local government.Purposes. The article is devoted to the problem of the formation of local authorities’ financial resources, local taxes and dues being their main source including land tax, to the process of formation of land taxation as well as to the definition of its role in the system of functioning of local authorities and state on the whole. The paper contains a comprehensive analysis of land taxation system, and shows its role and place in the state’s economic system. Proceeding from the analysis of the existing practice of land tax levying the author proves the necessity to reform land taxation, improve the mechanisms of levying land tax to insure full and timely income of land tax to local budgets.Results. Nature and structure of land taxation mechanism were proved and approaches concerning it construction in Ukraine were developed. Based on the realized analysis principal trends of collecting land tax in Ukraine were clarified, main factors which have the effect on forming of land taxation mechanism in our state were determined, problem aspects in land taxation which require improvement were emphasized. The mechanism of land tax application in foreign countries was investigated, main directions of land taxation processes optimization in Ukraine were proposed. It is proposed the improving the procedure for administering land tax in terms of conducting normative monetary valuation of land.Conclusions. It was proposed to improve the land tax in the area of its administration and the establishment of tax rates. The author has suggestions and proposals regarding legislation improvement in the sphere of legal regulation of land valuation in Ukraine.